Characterization of the Salt Overly Sensitive 1 (SOS1) Pathway Genes in Tea Plant (Cameliia sinensis) Under Environmental Stress - Shunkai Hu; Peishuo Jiang; Qirong Guo (Horticulturae)
Soil salinization poses a significant threat to tea plant (Camellia sinensis) production by compromising its bioactive compounds, such as polyphenols, L-theanine, and caffeine, which are key contributors to the plant’s health benefits and economic value. This study investigates the Salt Overly Sensitive 1 (SOS1) gene family, a critical salt-tolerance regulator in tea plants, to elucidate its role in maintaining quality under environmental stress. Genome-wide analysis identified 51 CsSOS1 genes, with phylogenetic and synteny analyses revealing strong evolutionary conservation with Populus trichocarpa and Arabidopsis thaliana. Promoter analysis detected stress- and hormone-responsive cis-elements, indicating adaptive functions in abiotic stress. Expression profiling demonstrated tissue-specific patterns, highlighting significant upregulation of CsSOS1-15 and CsSOS1-41 under salt and drought stress. Co-expression network analysis further linked CsSOS1 genes to carbohydrate metabolism, implicating their roles in stress resilience and secondary metabolite synthesis. Our findings provide molecular insights into CsSOS1-mediated salt tolerance, proposing potential targets for preserving bioactive compounds. This work facilitates developing salt-resistant tea plant cultivars to ensure sustainable production and quality stability amid environmental challenges.